Memaknai Ulang Ecclesia Domestica di Masa Pandemi Covid-19 - Antonius Galih Arga W. Aryanto; Martinus Joko Lelono (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. The pandemic covid-19 has compeled Catholic families to pray at home instead of going to the Church every Sunday, and it changed the expression of their faith. This new condition helped families to realize their role as formators of spiritual life for the family members. The purpose of this research was to look out how the social distancing effects the role of the family as the formator for faith formation of their children during pandemic covid-19. The research conducted by qualitative and quantitative approach toward fivety Catholic families. Through this research it was shown that during covid-19 pandemic family had a big chance of doing the role as the Church Family (ecclesia domestica) that emphasizing the future mission of the Church is depending on the family life. The Church Family is understood as the smallest cell of the Church as the sacrament, the visible sign of God, and becomes a place for encountering the faithful to Jesus Christ in the world.Abstrak. Pandemi covid-19 telah memaksa keluarga-keluarga Kristiani untuk beribadah di rumah dan mengubah cara menggereja mereka. Situasi itu menjadikan keluarga menyadari perannya sebagai pembina utama hidup rohani anggota keluarga. Penelitian ini bertujuan untuk melihat bagaimana pengaruh pembatasan sosial terhadap peran keluarga dalam pendidikan iman anak di masa pandemi covid-19. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif terhadap 50 keluarga Katolik. Melalui penelitian ini diperoleh gambaran bahwa dalam masa pandemic covid-19 ini keluarga berkesempatan menjalankan peran sebagai Gereja keluarga (ecclesia domestica) yang menekankan masa depan pewartaan Gereja adalah melalui hidup keluarga. Gereja keluarga dipahami sebagai sel terkecil yang menjadi bagian dari Gereja sebagai sakramen, tanda yang kelihatan dari Allah, dan menjadi medan pertemuan orang beriman dengan Yesus Kristus di dunia.